2022
DOI: 10.1186/s12889-022-14554-2
|View full text |Cite
|
Sign up to set email alerts
|

Time change in the distribution of physical activity and its correlates among retired older Swedish adults: a repeated cross-sectional study from a national survey

Abstract: Background Understanding how older adults spend time in moderate- to vigorous-intensity physical activity (MVPA) is crucial to understanding healthy ageing. This study connects 24-h time-use diary records of the daily activities of a sample of Swedish older adults to energy intensities. The aim was to: i) estimate the prevalence of Swedish older adults (aged 65–84 years) who achieved recommended daily levels of physical activity; ii) identify what domains of everyday life contribute to MVPA; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The greater amount of time spent exercising by men compared to women was also found in all occupational categories, although the effect size of the differences depended on the occupational category, which was maximized among students and also statistically significant among people with non-manual occupations and minimized among women and men with manual occupations. Other studies have also found that men spend more time exercising than women and that exercise is associated with younger age (Coen et al 2018;Forte et al 2023;Milanović et al 2013;Oliveira-Brochado et al 2017;Vilhelmson et al 2022). More physical exercise was associated with better self-reported health, fewer somatic symptoms, and greater well-being for both women and men.…”
Section: Discussionmentioning
confidence: 95%
“…The greater amount of time spent exercising by men compared to women was also found in all occupational categories, although the effect size of the differences depended on the occupational category, which was maximized among students and also statistically significant among people with non-manual occupations and minimized among women and men with manual occupations. Other studies have also found that men spend more time exercising than women and that exercise is associated with younger age (Coen et al 2018;Forte et al 2023;Milanović et al 2013;Oliveira-Brochado et al 2017;Vilhelmson et al 2022). More physical exercise was associated with better self-reported health, fewer somatic symptoms, and greater well-being for both women and men.…”
Section: Discussionmentioning
confidence: 95%
“…The observed long-term rise in the ATR incidence rate is presumably related to increased participation in sports or recreational activities among women and people at older ages, 28 30 evidenced by the higher incidence in women (58% vs 40% in men) and the shift in median injury age from 44 to 50 years. This observation is further substantiated by the fact that in 2002, the highest incidence was observed among patients aged 30–49 years, while by 2021, patients aged 40–80 years presented the highest increase and similar ATR incidence rates ( figure 2 ).…”
Section: Discussionmentioning
confidence: 99%